The Surprising Oceanography of the Gulf of Maine - Record, Nicholas; Tupper, Benjamin; Evanilla, Johnathan; Oliveira, Kyle; Ross, Camille; Ngai, Logan; Stamieszkin, Karen (Maine Policy Review, 2023)
The oceanography of the Gulf of Maine has changed in ways that have not been seen previously but that are likely to be more common in the future–changes like extreme rapid warming and declines in primary productivity. The changing oceanography has underpinned surprising losses in commercial stocks and endangered species. Because of the rapid rate of change, some have viewed the Gulf of Maine as a window into the ocean’s future, with the idea that lessons learned can be applied in places that have yet to experience similar rapid changes. We can examine the dynamics, origin, and implications of surprising oceanographic conditions–conditions that would have been considered unlikely based on recent prior experience. Based on a formal statistical definition of climate surprises, the frequency of oceanographic surprises in the Gulf of Maine is higher and has increased faster than what would be expected, even given underlying trends. Oceanographic surprises vary in character from one to the next and are often linked to larger scale shifting oceanography across the North Atlantic. The implications for ecological and human communities, industries, and conservation efforts imply a need for policies that consider adaptation to sudden events as well as long-term changes.